2014
DOI: 10.1097/mpg.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Zinc Supplementation and Growth in Extremely‐Low‐Birth‐Weight Infants With Chronic Lung Disease

Abstract: Objective Zinc deficiency causes growth deficits. Extremely-low-birth-weight (ELBW) infants with chronic lung disease (CLD), also known as bronchopulmonary dysplasia, experience growth failure and are at risk for zinc deficiency. We hypothesized that enteral zinc supplementation would increase weight gain and linear growth. Methods A cohort of infants was examined retrospectively at a single center between January 2008 and December 2011. CLD was defined as the need for oxygen at 36 weeks postmenstrual age. Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…Recent studies have also shown that enteral zinc supplementation helps in weight gain and growth of extreme low birth weight babies. (10) In conclusion oral zinc supplementation resulted in clinically important reduction in duration and severity of diarrhoea, hence the use of zinc as adjunctive therapy has the potential to improve the management of diarrhoea and increase survival in children. It helps reduction of morbidity and mortality due to diarrhoeal disease in children in our country who are likely to be malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that enteral zinc supplementation helps in weight gain and growth of extreme low birth weight babies. (10) In conclusion oral zinc supplementation resulted in clinically important reduction in duration and severity of diarrhoea, hence the use of zinc as adjunctive therapy has the potential to improve the management of diarrhoea and increase survival in children. It helps reduction of morbidity and mortality due to diarrhoeal disease in children in our country who are likely to be malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…Accretion of micronutrient stores occurs in the third trimester . Preterm infants are therefore at risk for micronutrient deficiency and require supplementation.…”
Section: Management Of En After Bowel Resectionmentioning
confidence: 99%
“…Este no documenta la conocida interacción que puede haber en la absorción de cationes divalentes: hierro, zinc y cobre, por lo que parece importante mantener esta posibilidad bajo protocolos clíni-cos. Por otra parte, el suplemento de Zn en niños con DBP tratados con diuréticos mejora el crecimiento y el estado nutricional de Zn, importante de considerar en el uso crónico de diuréticos 62 .…”
Section: Suplementos Vitaminas Y Mineralesunclassified
“…Se ha documentado una maduración más rápida de la succión nutritiva, acortamiento de la hospitalización y, en algunos estudios, mejor ganancia de peso 62 . La estimulación orokinésica perioral ayuda a una transición más rápida de sonda a oral.…”
Section: Aspectos Adicionales Del Manejo Nutricionalunclassified